EFFECTIVENESS AND PERSISTENCE OF GLP-1 RECEPTOR AGONIST TREATMENT AMONG PEOPLE WITH TYPE 2 DIABETES - Nadarajan, Lakshna Vani; Ooi, Ying Guat; Lim, Quan Hziung; Lim, Lee Ling (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION People with diabetes (PwD) have increased morbidity, mortality, and healthcare costs. Glucagon-like Peptide-1 Receptor Agonists (GLP-1RA) have revolutionized diabetes management by optimizing weight and glycemic control while providing cardiorenal protection. This study is designed to evaluate the effectiveness of GLP-1RA and identify predictors of treatment persistence among PwD. METHODOLOGY This retrospective cohort study at the Universiti Malaya Medical Centre included adult PwD prescribed with GLP-1RA between 2018-2023, excluding those with malignancy or post-bariatric surgery. Data on demographics, anthropometrics, comorbidities, biochemistry, and adverse events were extracted from electronic health records from the initiation of GLP-1RA until the last visit before December 31, 2023. A prescription refill gap of <90 days was classified as the persistent group (PG), while the remainder were categorised as the non-persistent Group (NPG). Generalised Linear Model (GLM) was used to determine factors associated with treatment persistence. RESULT Among 470 PwD analysed, the mean age was 59.1 ± 13.0 years, and 54.3% were female with a baseline BMI of 32.3 ± 6.6 kg/m2. 91% remained persistent with GLP-1RA. The majority were prescribed injectable semaglutide (55.7%), followed by injectable dulaglutide (27.4%), and oral semaglutide (13.2%). The PG had significantly greater reductions in both weight [-1.9 kg, 95%CI: -5.1,0.1; p = 0.03], and BMI [-0.78 kg/m², 95%CI:-1.94,0.04; p = 0.02] compared to the NPG. No significant differences were observed in HbA1c or blood lipid levels. Gastrointestinal side effects were more common among the NPG (37.2% vs 15%). Concomitant usage of SGLT2 inhibitors was the strongest predictor of treatment persistence (+16.2 weeks), with lower baseline HbA1c and urine albumin-creatinine ratio also linked to treatment persistence. CONCLUSION Our findings imply that PwD already on SGLT2 inhibitors, those with better glycaemic control and milder proteinuria at baseline are more likely to persist with their GLP-1 RA therapy. Further research incorporating mixed-model analyses and patient perspectives is needed to elucidate the underlying reasons for these associations.